"Grow by Looking": From Moral Perception to Pedagogical Responsibility. Issue 13 (December 2013) - Stengel, Barbara S.; Casey, Mary E.
To teach for instrumental and innovative growth for both student and teacher is not simply a technical challenge. It is a moral task, requiring intimacy in the service of developing autonomy. It involves moral sensitivity and moral perception in prompting and framing responsible pedagogical action. It is an emotionally fraught enterprise, one that runs headlong into the human resistance to development and growth (Bion, 1994). What follows is an uncovering of this pedagogical responsibility. As we shall show, the way in to the moral dimensions of a teacher's work is the same path that leads to academic effectiveness. Taking the moral seriously is not a diversion from the preparation and development of effective teachers, nor is it an added consideration; it is central to the very possibility of responsive and responsible education.